A composite indicator to measure universal health care coverage in India: way forward for post-2015 health system performance monitoring framework - Shankar Prinja; Rakesh Gupta; Pankaj Bahuguna; Atul Sharma; Arun Kumar Aggarwal; Amit Phogat; Rajesh Kumar (Health Policy Plan., 2017)
Background There is limited work done on developing methods for measurement of universal health coverage. We undertook a study to develop a methodology and demonstrate the practical application of empirically measuring the extent of universal health coverage at district level. Additionally, we also develop a composite indicator to measure UHC. Methods A cross-sectional survey was undertaken among 51 656 households across 21 districts of Haryana state in India. Using the WHO framework for UHC, we identified indicators of service coverage, financial risk protection, equity and quality based on the Government of India and the Haryana Government's proposed UHC benefit package. Geometric mean approach was used to compute a composite UHC index (CUHCI). Various statistical approaches to aggregate input indicators with or without weighting, along with various incremental combinations of input indicators were tested in a comprehensive sensitivity analysis. Findings The population coverage for preventive and curative services is presented. Adjusting for inequality, the coverage for all the indicators were less than the unadjusted coverage by 0.1-6.7% in absolute term and 0.1-27% in relative term. There was low unmet need for curative care. However, about 11% outpatient consultations were from unqualified providers. About 30% households incurred catastrophic health expenditures, which rose to 38% among the poorest 20% population. Summary index (CUHCI) for UHC varied from 12% in Mewat district to 71% in Kurukshetra district. The inequality unadjusted coverage for UHC correlates highly with adjusted coverage. Conclusion Our paper is an attempt to develop a methodology to measure UHC. However, careful inclusion of others indicators of service coverage is recommended for a comprehensive measurement which captures the spirit of universality. Further, more work needs to be done to incorporate quality in the measurement framework.
Keywords: Adolescent health; Burden of disease among Indian adolescents; Non communicable disease